MUSYKILĀT ISTIKHDĀM AL-ṬARĪQAH AL-MUBĀSYIRAH FĪ TA’LĪM AL-MUṬĀLA’AH WA ḤULŪLUHĀ - Ma'afi, Rif'at Husnul; Salma, Ria Fauziah (Idrak: Journal of Islamic Education, 2019)
Muthala?ah is one of the most influential lessons in teaching Arabic Language, especially at the Islamic Boarding School Darussalam Gontor. This Institute used the direct method of teaching Muthala?ah. But the application of it was not complete and problems emerged. The aim of this research is to uncover the problems of using the direct method in teaching Muthala?ah and their solutions for students of class one intensive at Islamic Teachers Training College Darussalam Gontor for Girls First Campus academic year 1438-1439. There were problems of using the direct method of teaching Muthala?ah for students of class one intensive came from the teachers and the students as the pupils who do the educational process. But, because of the important of enough Arabic Language knowledge? students, they need the responsible of branches as their Arabic Language teacher outside classroom. So, the solutions of the problems came to teachers, students and responsible of branches